Approaches to Preventing Intrapartum Fetal Injury - Schifrin, Barry S.; Koos, Brian J.; Cohen, Wayne R.; Soliman, Mohamed (Frontiers in Pediatrics, 2022)
Electronic fetal monitoring (EFM) was introduced into obstetric practice in 1970 as a test to identify early deterioration of fetal acid-base balance in the expectation that prompt intervention (“rescue”) would reduce neonatal morbidity and mortality. Clinical trials using a variety of visual or computer-based classifications and algorithms for intervention have failed repeatedly to demonstrate improved immediate or long-term outcomes with this technique, which has, however, contributed to an increased rate of operative deliveries (deemed “unnecessary”). In this review, we discuss the limitations of current classifications of FHR patterns and management guidelines based upon them. We argue that these clinical and computer-based formulations pay too much attention to the detection of systemic fetal acidosis/hypoxia and too little attention not only to the pathophysiology of FHR patterns, but to the provenance of fetal neurological injury, and to the relationship of intrapartum injury to the condition of the newborn. Though they do not reliably predict fetal acidosis, FHR patterns, properly interpreted in the context of the clinical circumstances do reliably identify fetal neurological integrity (behavior) and are a biomarker of fetal neurological injury (separate from asphyxia). They provide insight into the mechanisms and trajectory (evolution) of any hypoxic or ischemic threat to the fetus and have particular promise in signaling preventive measures 1) to enhance outcome, 2) to reduce the frequency of “abnormal” FHR patterns that require urgent intervention, 3) and to inform the decision to provide neuroprotection to the newborn.